2013
DOI: 10.1111/are.12209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soluble dietary cellulose on specific growth rate, survival and digestive enzyme activities in three freshwater crayfish (Cherax) species

Abstract: The current study evaluated the effect of soluble dietary cellulose on growth, survival and digestive enzyme activity in three endemic, Australian freshwater crayfish species (redclaw: Cherax quadricarinatus, marron: C. tenuimanus, yabby: C. destructor). Separate individual feeding trials were conducted for late-stage juveniles from each species in an automated recirculating freshwater, culture system. Animals were fed either a test diet (TD) that contained 20% soluble cellulose or a reference diet (RD) substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
7
3
Order By: Relevance
“…The results of Dammannagoda et al . () are in disagreement with our results because they observed that C. quadricarinatus adults showed significantly higher protease and amylase activities when fed the reference diet. The proteinase activity in animals of D group fed with RF showed relative high levels than those reported by Dammannagoda et al .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The results of Dammannagoda et al . () are in disagreement with our results because they observed that C. quadricarinatus adults showed significantly higher protease and amylase activities when fed the reference diet. The proteinase activity in animals of D group fed with RF showed relative high levels than those reported by Dammannagoda et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with Lee et al (1984) and Gamboa-Delgado et al (2003), who observed that digestive enzymes activity in Litopenaeus vannamei varies in relation to the protein level in the diet and body weight. The results of Dammannagoda et al (2015) are in disagreement with our results because they observed that C. quadricarinatus adults showed significantly higher protease and amylase activities when fed the reference diet. The proteinase activity in animals of D group fed with RF showed relative high levels than those reported by Dammannagoda et al (2015) in the same species.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations